PENGARUH PENGGUNAAN MEDIA VIDEO COMPACT DISK (VCD) TERHADAP HASIL BELAJAR SHOOTING BOLA TANGAN DALAM PEMBELAJARAN PENDIDIKAN JASMANI, OLAHRAGA DAN KESEHATAN (STUDI PADA SISWA KELAS XI SMA NEGERI 22 SURABAYA) - CHRISTA HARDINI, EKA (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstract Physical education is the part of ongoing education that involving the movement of the human body that lead to the result of the behaviour changing that head for the complete physical health. For the such porpose, the theacer must be able to give the variation to the students study progress, in order that the students can receive the teaching very well. One of the many ways is choosing the compact disc video media as the information madiator, by using that media researcher hope the learning process can be held effectively.           This research using phenomenological descriptive quantitative experiment, and the research design is randomized group control pre test post test. The population of this research is the students of 22nd state high school of Surabaya XI class as a whole. The sample choosing use cluster random sampling method on the amount of 71 students. Than parted into two parts 35 students as the experiment group and 36 students as the control group. The instrument of this research is hand ball shooting practice, Have purpose to knowing final learn of hand ball shooting by students of 22nd state high school of Surabaya class XI.           The researcher take the conclution Based on the Statistic calculation result that there is no effect of the using of Compact disc video media on the hand ball shooting training result in the physical education, sport, and health that can be proved from the Tcount 1.9847<ttable 1.990. Keywords : compact disc video media, training result, hand ball shooting